Rancang Bangun Aplikasi Penilaian Kinerja Karyawan Berbasis Website Menggunakan Metode 360 Derajat (Studi Kasus : PT Surya Segara Safety Marine) - Refo Fattahillah; Slamet A; I Gusti Ngurah Alit Widana Putra (Jurnal Sistem Informasi Universitas Dinamika, 2021)
Performance appraisal is one way to determine the quality of employee in the company. The performance appraisal process at PT Surya Segara Safety Marine often experiences several problems such as the submission of employee performance appraisal reports that are not on time because the calculation process from the human resources development staff has not used the system. In addition, there is no appropriate appraisal method to assess employees which causes appraisal to be a little difficult. The appraisal applied by the company only uses one side as an appraiser, namely the head of the department, which reduces employee motivation. This study aims to obtain an overview of the employee performance appraisal application through the 360 degree method in PT Surya Segara Safety, so that it can help companies to present performance appraisals for human resource development. The study used a qualitative approach through data collection techniques using observation and interviews. Application creation method with Waterfall System Development Life Cycle (SDLC). The results showed that the performance appraisal application through the 360 degree method can provide performance appraisal notifications as a reminder so that users immediately carry out the performance appraisal process. The performance appraisal application through the 360 degree method provides 4 answer options that make the assessment results more varied and include assessment indicators so that the assessment becomes objective because it takes opinions or feedback from three parties, namely head of division, co-workers, and theirself. It is hoped that this method can make the performance appraisal at PT Surya Segara Safety Marine more objective and can restore employee motivation compared to previous assessments.